Analysis of Salary and Wage Accounting Information Systems in The Framework of Internal Control at PTPN IV Medan - Zhafran, Faras Abiyyu; Nasution, Juliana (widya balina, 2023)
The structure of interrelated procedures in the payroll and wage accounting system is based on a comprehensive plan for carrying out the company's core operations and functions. Interior control is essential for this framework, including hierarchical designs, techniques, and activities consolidated to safeguard organization resources, check the unwavering quality and exactness of bookkeeping information, further develop capability, and guarantee consistency with the executive guidelines. The compensation and pay bookkeeping data framework at PTPN IV Medan isn't completely as per the hypothesis that upholds it. Despite the fact that she had been helped by unique mark programming, Ms. Office Excel, dan Accurate Accounting System, related works actually have not arrived at the best level. As a result, the payroll and wage accounting information system's internal control can still be improved, particularly with regard to the division of labor in the financial sector. This can be accomplished by creating new sections in accordance with applicable theory, such as the employment function, the PPh21 function, and other functions, to ensure this system's internal control is more efficient.